2012
DOI: 10.1080/00071668.2012.719148
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary glutamine and gamma-aminobutyric acid on meat colour, pH, composition, and water-holding characteristic in broilers under cyclic heat stress

Abstract: 1. An experiment was conducted to evaluate the effects of dietary glutamine (Gln, 0 and 5 g/kg) and gamma-aminobutyric acid (GABA, 0 and 100 mg/kg) on raw breast meat colour, pH, composition and water-holding characteristic of broilers under cyclic heat stress (HS). 2. A total of 360 21-d-old Arbor Acres male chicks were randomly assigned to 5 treatment groups (6 replicates of 12 birds per cage). The positive control (PC) broilers were kept in a thermoneutral chamber (22-24°C) and fed on the basal diet. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(40 citation statements)
references
References 57 publications
3
35
0
1
Order By: Relevance
“…This reduction is necessary for the conversion of muscle into meat (Dransfield and Sosnicki, 1999;Lehninger et al, 2008). Chronic exposure to high ambient temperatures, as occurred in the present study, may have lead to an exhaustion of muscle glycogen reserves in vivo, resulting in meat with higher pH (Mckee and Sams, 1997;Dai et al, 2012). Acute heat stress, in contrast, has been associated with faster postmortem pH decline and lower pH (Debut et al, 2003).…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…This reduction is necessary for the conversion of muscle into meat (Dransfield and Sosnicki, 1999;Lehninger et al, 2008). Chronic exposure to high ambient temperatures, as occurred in the present study, may have lead to an exhaustion of muscle glycogen reserves in vivo, resulting in meat with higher pH (Mckee and Sams, 1997;Dai et al, 2012). Acute heat stress, in contrast, has been associated with faster postmortem pH decline and lower pH (Debut et al, 2003).…”
Section: Discussionmentioning
confidence: 53%
“…Meat discoloration originates from the oxidation of ferrous myoglobin derivatives to metmyoglobin. Several studies have associated chronic heat stress with increased breast meat lightness (Aksit et al, 2006;Lu et al, 2007;Dai et al, 2012), but the effects on redness and yellowness were variable. Similar to the present study, Zhang et al (2012) reported decreased redness and unchanged yellowness under chronic heat stress, but Aksit et al (2006) found increased redness and Lu et al (2007) did not detect any changes in these two color measurements in the breast meat of Arbor Acres chickens under constant heat stress.…”
Section: Discussionmentioning
confidence: 99%
“…Several researchers have used essential amino acids in an attempt to overcome heat-stress problems in poultry (Mendes et al, 1997;Rose and Uddin, 1997;Brake et al, 1998;Willemsen et al, 2011;Dai et al, 2012). However, in addition to essential amino acids, non-essential amino acids may also reduce the effects of psychological and physiological stress in chicks (Erwan et al, 2012(Erwan et al, , 2014a, since their levels have been found to be modified under heat stress Ito et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Nutrients, especially amino acids, are widely applied as anti-stress agents with regard to psychological and physiological stress (Yamane et al, 2009;Hamasu et al, 2010;Erwan et al, 2012Erwan et al, , 2014b. Amino acid in particular essential amino acids supplementation has been performed in order to overcome heat-stress problems in birds (Mendes et al, 1997;Brake et al, 1998;Willemsen et al, 2011;Dai et al, 2012). However, not only essential amino acids, but also non-essential amino acids may be useful to mitigate heat-stress problems.…”
Section: Introductionmentioning
confidence: 99%